Activating Change: The Role of Information and Beliefs in Social Activism - Farzana Afridi; Ahana Basistha; Amrita Dhillon; Danila Serra (Institute of Labor Economics (IZA), 2023)
What motivates individuals to participate in social activism? Do awareness campaigns and information about others' willingness to act play a role? We conduct an online experiment within a survey of nearly 2000 Indian men, focusing on activism to combat health sector fraud during the COVID-19 pandemic. In different treatment groups, we either provide information about the social problem, correct misaligned beliefs about others' willingness to act, or both. Participants are then cross-randomized to engage in one of three forms of activism: signing a petition, making a donation to an NGO fighting for the cause, or watching a video on ways to support the cause. We also experimentally examine the impact of allowing subjects to choose between the three forms of activism. Providing information and correcting downward biased beliefs about others increases petition signing, but has no impact on donations and video viewing. Giving participants a choice of actions decreases the probability of any single action being taken up. Our comprehensive examination of the factors influencing engagement in different forms of activism within a unified framework generates insights on the motivations behind participation in collective efforts for social change.
Keywords: D73; D83; I15; P0; 330; activism; information; beliefs; experiment